Differences in Recurrence Rate and De Novo Incontinence after Endoscopic Treatment of Vesicourethral Stenosis and Bladder Neck Stenosis - Kranz, Jennifer; Reiss, Philipp C.; Salomon, Georg; Steffens, Joachim; Fisch, Margit; Rosenbaum, Clemens M. (Frontiers in Surgery, 2017)
Objectives: The objective of this study was to compare the recurrence rate and de-novo incontinence after endoscopic treatment of vesicourethral stenosis (VUS) after radical prostatectomy (RP) and for bladder neck stenosis (BNS) after transurethral resection of the prostate (TURP). Methods: Retrospective analysis of patients treated endoscopically for VUS after RP or for BNS after TURP at three German tertiary care centers between March 2009 and June 2016. Investigated endpoints were recurrence rate and de-novo incontinence. Chi-squared tests and t-tests were used to model the differences between groups. Results: A total of 147 patients underwent endoscopic therapy for VUS (59.2%) or BNS (40.8%). Mean age was 68.3 years (range 44-86), mean FU 27.1 months (1-98). Mean time to recurrence after initial therapy was 23.9 months (1-156), mean time to recurrence after prior endoscopic therapy for VUS or BNS was 12.0 months (1-159). Patients treated for VUS underwent significantly more often radiotherapy prior to endoscopic treatment (33.3 vs. 13.3%; p=0.006) and the recurrence rate was significantly higher (59.8 vs. 41.7%; p=0.031). The overall success rate of TUR for VUS was 40.2%, success rate of TUR for BNS was 58.3%. TUR for BNS is significantly more successful (p=0.031). Mean number of TUR for BNS vs. TUR for VUS in successful cases was 1.5 vs. 1.8, which was not significantly different. The rate of de-novo incontinence was significantly higher in patients treated for VUS (13.8 vs. 1.7%; p=0.011). After excluding those patients with radiotherapy prior to endoscopic treatment, the recurrence rate did not differ significantly between both groups (60.3% for VUS vs. 44.2% for BNS; p=0.091), whereas the rate of de-novo incontinence (13.8 for VUS vs. 0% for BNS; p=0.005) stayed significantly higher in patients treated for VUS. Conclusions: Most patients with BNS are successfully treated endoscopically. In patients with VUS, the success rate is lower. Both stenoses differ with respect to de-novo incontinence. Patients must be counselled regarding the increased risk of de-novo incontinence after endoscopic treatment of VUS, independent of prior radiotherapy. Longer follow-up is warranted to address long-term outcomes.